Implementasi Nilai-Nilai Kebangsaan Berbasis UUD 1945 dalam Penerapan Strategi Manajemen Sekuriti untuk Mencapai Zero Accident: Studi Kasus pada Industri Manufaktur PT Denso Indonesia - Suhartini; Edy Soesanto; Wike Apriliansyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In the context of the industrial revolution 4.0 and the introduction of new technology, workplace safety has become a crucial aspect, especially in the manufacturing sector. In facing these challenges, it is important for the manufacturing industry to integrate proactive and integrated safety strategies. Employee safety and welfare is not only a moral responsibility, but also reflects the company's commitment to protecting human assets, in accordance with the values and principles of the 1945 Constitution. This research aims to provide a systematic, factual and accurate picture of strategy implementation safety management at PT Denso Indonesia in achieving Zero Accident, in line with Law of the Republic of Indonesia Number 1 of 1970 concerning Work Safety. The research results highlight that most work processes at PT Denso Indonesia have a high level of risk, however, the company has adopted safety management strategies to prevent accidents that are detrimental to employees and the company. In implementing this strategy, PT Denso Indonesia prioritizes national values by considering the principles of the 1945 Constitution. Efforts such as Safety Dojo and SCW are used to improve safety, while technology such as PIR sensors are also applied to prevent accidents. Success in achieving Zero Accident is influenced by consistency, employee participation, and strategy integration into a company culture that is based on national values. Thus, safety in the workplace is not only a goal, but also reflects the spirit of harmony between the interests of the company, employees and the nation, in accordance with the principles of the 1945 Constitution.